A Study on Impact of Mass Media on Rural Women: Exploring the Effects of Mass Media on Rural Women (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Mass media influences society including women very much. Mass media include radio, press, television, Information and Communication Technology (ICT) applications such as internet, social networking, etc. The mass media have both negative as well as positive effects on society. Mass media of communication are very crucial for nation building and national development in any developing society. The creations of current science and innovation are mass-media. They play a significant function in advising, educating and entertaining individuals. The present study takes into account the impact of mass media on rural women.